Successful Use of Extracorporeal Membrane Oxygenation for Respiratory Failure Caused by Mediastinal Precursor T Lymphoblastic Lymphoma - Masafumi Oto; Kyoko Inadomi; Toshiyuki Chosa; Shima Uneda; Soichi Uekihara; Minoru Yoshida (Case Reports in Medicine)
Precursor T lymphoblastic lymphoma (T-LBL) often manifests as a mediastinal mass sometimes compressing vital structures like vessels or large airways. This case was a 40-year-old male who developed T-LBL presenting as respiratory failure caused by mediastinal T-LBL. He presented with persistent life threatening hypoxia despite tracheal intubation. We successfully managed this respiratory failure using venovenous (VV) ECMO. Induction chemotherapy was started after stabilizing oxygenation and the mediastinal lesion shrank rapidly. Respiratory failure caused by compression of the central airway by tumor is an oncologic emergency. VV ECMO may be an effective way to manage this type of respiratory failure as a bridge to chemotherapy.